Corporate Sale-and-Leasebacks and Shareholder Wealth. - Polonchek, John A; Slovin, Myron B; Sushka, Marie E (Journal of Finance, 1990)
In this paper, the authors examine the market valuation effects of corporate saleleasebacks. Specifically, they test whether such transactions offer a net benefit to lessees or lessors by evaluating the impact on share prices from announcements of saleleasebacks of major corporate assets. Their evidence indicates that the announcements are associated with positive abnormal returns to lessees. They conclude that this positive market reaction results from an overall reduction in the present value of expected taxes occasioned by the transactions. The evidence also suggests that the gains from saleleasebacks accrue solely to lessee firms.